Curvilinear relationship between ethical leadership and creativity within the Colombian electricity sector. The mediating role of work autonomy, affective commitment, and intrinsic motivation - Santiago-Torner, Carlos (Iberoamerican Journal of Development Studies, 2023)
The Colombian electricity sector has promoted transparency collectively since 2015 with good practices and an ethical leadership style as the main sources of growth. Together, the situation of global uncertainty in which we have been immersed since 2020 has made creativity one of the main organizational competitive advantages. For this reason, this research aims to consider whether the prevailing ethical leadership style in the sector studied is related to creativity through work autonomy, affective commitment, and intrinsic motivation as mediating variables, using a quantitative and cross-sectional methodological scheme with a sample of 448 participants. From the results, it is highlighted that the association between ethical leadership and creativity is not linear but curvilinear. In addition, the low structuring of tasks and empowerment, together with the strengthening of the follower’s skills and the relationships of trust that strengthen their self-development and selfefficacy, improve work autonomy, intrinsic motivation, and affective commitment, which makes the mediation between leadership more significant. ethics and creativity, which in turn is strengthened through seven indirect effects.
Keywords: ethical leadership; work autonomy; affective commitment; intrinsic motivation; creativity; ethics